(3cTa GdbfGY aj QSe GdCQHGYs - (3eMeO Hf eMeO Hf eMeO GdHcQj GdTGaYj, CHh YHO Gddg,J (B840 (3g` s
(3ChdgG (B:s
(3HYO GdOjGLg (B: (3agPg OjHGLg dWjag SejJgG HcTa GdbfGY ai QSe GdCQHGY hPcQJ ajgG GdeSJYed ZGdHkG NeSI hYQTjf BdI ef PhGJ GdChVGY GSJaOJgG ef GdeTGjN hGdGdGJ HGdcTa hGdCWdGY s
(3BNQgG (B:s
(3GdfU ZjQ cGed EdjgG ef GdbhS ai GdebfWQGJ JLO LjHg hHYV GdCYeGd s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B273s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B127 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B87 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1494s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3Gdadcs